Blood brain barrier: A review of its anatomy and physiology in health and disease. Issue 6 (18th October 2018) - Sharif, Yousra; Jumah, Fareed; Coplan, Louis; Krosser, Alec; Sharif, Kassem; Tubbs, R. Shane
Abstract : The blood–brain barrier (BBB) is the principal regulator of transport of molecules and cells into and out of the central nervous system (CNS). It comprises endothelial cells, pericytes, immune cells, astrocytes, and basement membrane, collectively known as the neurovascular unit. The development of the barrier involves many complex pathways from all the progenitors of the neurovascular unit, but the timing of its formation is not entirely known. The coordinated activities of all the components of the neurovascular unit and other tissues ensure that materials required for growth and maintenance are allowed into the CNS while extraneous ones are excluded. This review summarizes current knowledge of the anatomy, development, and physiology of the BBB, and alterations that occur in disease conditions. Clin. Anat. 31:812–823, 2018. © 2018 Wiley Periodicals, Inc.